Association Between Early Cognitive Impairment and Midterm Functional Outcomes Among Chinese Acute Ischemic Stroke Patients: A Longitudinal Study - Li, Juan; Wang, Jing; Wu, Bei; Xu, Hanzhang; Wu, Xiongfeng; Zhou, Lanshu; Deng, Benqiang (Frontiers in Neurology, 2020)
Backgroud: The association between early cognitive impairment and mid-term functional outcomes among Chinese acute ischemic stroke (AIS) patients has not been fully explored. Methods: A longitudinal survey focusing on Chinese AIS patients was conducted in three Stroke units in Shanghai, China (July 2016 to June 2017). A total of 185 eligible participants were interviewed at four waves, acute stage, 1, 3, 6 months after onset. The functional outcomes of patients were measured by modified Rankin Scale (mRS) and Barthel Index (BI). Their cognitive function was measured by Montreal Cognitive Assessment, ChangshaVersion (MoCA-CS) within 7 days after stroke. Functional outcome was evaluated using mRS and BI at each wave of the interviews. Covariates included patient’s demographic characteristics, socioeconomic status, clinical characteristics of stroke, vascular risk factors, receiving rehabilitation after discharge from acute hospital and recurrence. Generalized linear mixed modles and general linear mixed models were applied. Results: The prevalence of cognitive impairment at acute stage of stroke among these participants was 88.1%. The risk of disability(mRS 2-5) of all participants after stroke decreased over time (OR= 0.491, 95%CI= 0.401-0.603). The risk of disability among those with cognitive impairment increased compared to those with normal cognition (OR= 7.384, 95%CI= 1.041-52.407).The BI score of all participants increased over time after controlling for covariates (β= 1.51, p<0.01). The BI score of those with cognitive impairment was lower than those with normal cognition over the follow-up period after controlling for other covariates (β=-8.11, p<0.05). Conclusions: This study showed that early cognitive impairment was associated with higher risk of disability and poor ADL among Chinese AIS patients. Further studies are needed to examine the linkage between multi-domain cognitive impairment and long-term disability and ADL among stroke survivors by neurophychological test batteries.